Emerging technologies and applications: comprehensive & organized - Guha Neogi, Subhrendu (Aryan pub., 2026)
Emerging technologies and applications: comprehensive & organized / Guha Neogi, Subhrendu. -- Kolkata: Aryan pub., 2026 006.3 G942 No. of Copies : 1